Meta-Analysis of Re-perfusion Injury and Ischaemic Conditioning in Limb Surgery - Utomo, Pamudji Utomo; Yudistira, Mochamadsyah Beizar (Indonesian Journal of Medicine, 2021)
Background: Pneumatic tourniquet commonly used for orthopedic surgery is associated with morbidity related to ischemia-reperfusion injury. Ischaemia conditioning (IC) had shown beneficial effects to attenuate these outcomes. This study aimed to systematically review the evidence of IC effect on outcomes of the patient undergoing orthopedic surgery.Subjects and Method: This was a systematic review and Meta-Analysis conducted through the online database search from PubMed, Central, Clinicaltrials.gov, and Scopus with topics related to IC and all possible orthopedic surgical interventions. Articles were searched with Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) protocols used keywords "Ischemic conditioning," "Reperfusion injury," "Orthopaedic surgery." The data were extracted from the eligible study within inclusion and exclusion criteria. Two independent reviewers collected the study characteristics. Each study was examined for the risk of bias. The pooled data were analyzed using RevMan 5.3 in Standardized Mean Difference (SMD) as a summary measure with 95% Confidence Interval (CI).Results: Out of 12 eligible studies collected for qualitative analysis, eight studies with the same outcomes were analyzed for quantitative analysis. A random-effect model was used for analysis with high heterogeneity. The pooled SMD data for IC compared to control for postoperative pain were -0.50 (95% CI= -0.95 to 0.06; p<0.001). Outcome measures for hemodynamic stability, systemic inflammation, and end-organ injury were pooled with MD= 4.81 (95% CI= 3.19 to 6.44); SMD= -1.33 (95% CI= -2.06 to -0.60); SMD= 0.15 (95% CI= -0.14 to 0.71); respectively.Conclusion: Ischaemic conditioning significantly reduces postoperative pain, inflammation response and maintains hemodynamic stability. A better study design with a higher population number is needed for further study.Keywords: ischaemic conditioning, reperfusion injury, orthopedic surgery, Meta-AnalysisCorrespondence: Pamudji Utomo. Dr. Soeharso Ortopedic Hospital. 157th Ahmad Yani St. Sukoharjo 57162, Central Java, Indonesia. pamudji_utomo@staff.uns.ac.id.Indonesian Journal of Medicine (2021), 06(03): 271-284 https://doi.org/10.26911/theijmed.2021.06.03.04